LEGAL LIABILITY OF STREAMERS RECIPIENTS OF DONATIONS FROM ONLINE GAMBLING SITES - Dwishar Kharismanto; Rifqi Ridlo Phahlevy (International Journal of Business, Law and Political Science, 2024)
Technological advances through social media have made a lot of progress.This has led to many changes in people's lives, such as donations as a means of collecting funds which used to be done conventionally has now become digital. The existence of an online donation platform raises a new problem. Donation providers often abuse their authority to gain additional profits through online gambling advertisements distributed through their YouTube accounts. Departing from these problems, the author conducted this research using normative juridical methods. Based on research, the author found that the act of spreading online gambling advertisements through the YouTube live streaming donation system violates the provisions stipulated in Article 27 Paragraph (2) of Law Number 19 of 2016 with the threat of imprisonment for a maximum of 6 years with a fine of IDR. 1 Billion. The government, as the party that has the authority to enforce the law against individual content creators who disseminate online gambling advertisements through a donation system, is expected to act decisively to reduce the increase in the number of online gambling cases.